MAPPING AND ANALYSING NEGATIVE CAMPAIGNS AGAINST PALM OIL - Judijanto, Loso (Seven Editora, 2026)
The palm oil industry has been the subject of persistent negative campaigns, particularly in international media and advocacy discourse, often linking it to deforestation, biodiversity loss, and climate change. These narratives, while partially supported by scientific findings, are frequently influenced by political, economic, and ideological agendas, leading to polarized global perceptions. This study aims to systematically map and analyze how negative campaigns against palm oil have been framed, disseminated, and interpreted within peer-reviewed academic literature. Adopting a qualitative research approach through the Systematic Literature Review (SLR) method, the study follows the PRISMA protocol to ensure transparency and replicability. Literature was sourced exclusively from the ScienceDirect database, using a Boolean keyword combination to refine search results for “negative campaigns,” “media framing,” and “public perception” related to palm oil. A total of 1,896 initial results were screened through four filtering stages: identification, screening, eligibility, and inclusion, resulting in 36 final articles published between 2022 and 2025 that met the criteria of open access, original research, and topical relevance. Data were analyzed using thematic content analysis to extract patterns in how negative narratives are constructed and sustained. The results reveal five dominant themes: environmental degradation framing, socio-economic marginalization, media amplification mechanisms, geopolitical protectionism, and response gaps from producing countries. The study concludes that negative campaigns are often selectively constructed, lacking a holistic view of comparative sustainability. Future research should examine longitudinal changes in narrative framing and investigate counter-framing strategies that more equitably include producer voices.DOI: https://doi.org/10.56238/sevened2026.008-065